Quality characteristics and antioxidant properties of sponge cakes containing black carrot (Daucus carota ssp. sativus var. atrorubens Alef) flour - Song, Ka-Young; O, Hyeonbin; Zhang, Yangyang; Kim, Young-Soon (Progress in Nutrition, 2016)
Black carrot contains limited calories, plentiful simple sugars, dietary fiber, and anthocyanins. It also attenuates retrogradation of cake and has an anticancer effect. Our aim was to find an optimal proportion of black carrot flour (BCF) in sponge cake. Black carrot sponge cakes were prepared by 0%, 2%, 4%, 6%, and 8% replacement of wheat flour with BCF and were designated as the Control (without black carrot flour), BCF2, BCF4, BCF6, and BCF8, respectively. Control and BCF6 showed low specific gravity: 0.45 and 0.47, respectively. The baking loss was significantly lower (6.88%) in BCF6. The L, a, and b values of color tended to decrease with increased proportion of BCF, except for the a value of crumbs. The Control and BCF8 were slightly alkaline: pH 7.50 and 7.09, respectively. Hardness was the lowest in BCF4 (153.57 g/cm2), followed by that in BCF6 (163.50 g/cm2). The polyphenol content of sponge cakes supplemented with BCF increased with increasing proportion of BCF, as did the scavenging activity toward the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical. A seven-point test showed that BCF6 had the best flavor and sweetness. Our data indicate that the optimal proportion of BCF for sponge cake in terms of rheological properties and antioxidant activity is 6%.